Sensing characteristics of nanocrystalline bismuth oxide clad-modified fiber optic gas sensor. (August 2017) - Manjula, M.; Karthikeyan, B.; Sastikumar, D.
Abstract: Gas sensing properties of nanocrystalline bismuth oxide clad – modified fiber optic sensor is reported for ammonia, ethanol, methanol and acetone gasses at room temperature. The output of sensor increases or decreases for certain gasses when the concentration of the gas is increased. The sensor exhibits high response and good selectivity to methanol gas. Time response characteristics of the sensor are also reported. Highlights: Bismuth oxide clad modified fiber optic gas sensor is proposed. The proposed sensor operates at room temperature. The sensor exhibits gas selectivity for methanol along with ethanol and ammonia.